Coastal altimetry - Vignudelli, Stefano (Springer, 2011)
Preface.- Chapter 1: Altimetry Missions: past, present and future.- Chapter 2: From Research to Operations: The USDA Global Reservoir and Lake Monitor.- Chapter 3: User requirements in the coastal ocean for satellite altimetry.- Chapter 4: Re-tracking altimeter waveforms near the coasts: A review of retracking methods and some applications to coastal waveforms.- Chapter 5: Range and geophysical corrections in coastal regions - and implications for mean sea surface determination.- Chapter 6: Tropospheric corrections for coastal altimetry.- Chapter 7: Surge Models as Providers of Improved "Inverse Barometer Corrections" for Coastal Altimetry Users.- Chapter 8: Tide Predictions in Shelf and Coastal Waters: Status and Prospects.- Chapter 9: Post-processing altimeter data toward coastal applications and integration into coastal models.- Chapter 10: Coastal Challenges for Altimeter Data Dissemination and Services.- Chapter 11: In situ Absolute Calibration and Validation - A link from coastal to open-ocean altimetry.- Chapter 12: Introduction and assessment of improved coastal altimetry strategies: case-study over the North Western Mediterranean Sea.- Chapter 13: Satellite Altimetry Applications in the Caspian Sea.- Chapter 14: Satellite Altimetry Applications in the Black Sea.- Chapter 15: Satellite Altimetry Applications in the Barents and White seas.- Chapter 16: Satellite Altimetry Applications off the Coasts of North America.- Chapter 17: Evaluation of Retracking Algorithms over China and Adjacent Coastal Seas.- Chapter 18: Satellite altimetry for geodetic, oceanographic and climate studies in the Australian region.- Chapter 19: Lakes studies from satellite altimetry.- Chapter 20: The Future of Coastal Altimetry.